Adaptasi Masyarakat Di Sekitar Kawasan Wisata Religi Pamijahan Terhadap Covid-19 - Adisty Rizqi Fitriani; Siti Agnia; Doni Yudistira; Moch. Rusli Aprilian; Syahrul Ramdani; Yani Sri Astuti (Pusat Riset dan Inovasi Nasional, 2024)
Pamijahan religious tourism is a tourist attraction that is often visited by domestic tourists for pilgrimage. However, on March 2, 2020 the first case of Covid-19 occurred in Indonesia. This had an impact on community activities with the establishment of lockdown policies and travel restrictions as an effort to prevent the wider spread of Covid-19. The research method used is a qualitative method through direct observation with in-depth interviews. This research aims to examine the impact and adaptation of the community to Covid-19 in Pamijahan Village. Based on the results of the research, it is known that when the lockdown policy and travel restrictions were enforced, the economy of the community around the Pamijahan tourist attraction was almost paralyzed, because the community only relied on sources of income from the tourist attraction. However, some of them have other sources of income to fulfill their needs.